Diabetes-Related Web Sites - Linda B. Bobroff; Nancy J. Gal (EDIS)
FCS-8875, a 1-page fact sheet by Linda B. Bobroff and Nancy J. Gal, provides a list of recommended websites to help people with diabetes increase their knowledge, better communicate with their health care teams, and make important lifestyle choices that allow them to live well with diabetes and reduce long-term health risks. Published by the UF Department of Family Youth and Community Sciences, August 2009.